Star of the week - Adderson, Caroline, 1963- (Adderson, Caroline, 1963- Jasper John Dooley, 2012)
At last, it's Jasper John Dooley's turn to be Star of the Week at school. Unfortunately, nothing turns out as planned. His Show and Tell falls flat. A new baby at his friend Ori's house steals his spotlight. And worst of all, the new baby has only-child Jasper wondering if his own family is too small. When Jasper decides to build himself a brother (named Earl) out of wood, Earl's schoolyard shenanigans send Jasper to the principal's office! But with a little help from family and friends, things turn around for Jasper. And by the time Friday arrives, he is once again sure that he has what it takes to be a star.